Removal of humic substances by electrocoagulation (EC) process and characterization of floc size growth mechanism under optimum conditions - Ulu, Feride; Barisci, Sibel; Kobya, Mehmet; Sarkka, Heikki; Sillanpaa, Mika (Elsevier Science Bv, 2014)
The aim of this study was to evaluate the treatability of synthetically prepared humic acid solution by electrocoagulation (EC) process in batch mode using aluminum and iron electrodes. The effect of the main parameters pH, current density, and electrode type on natural organic matter (NOM) removal was investigated. Also, in order to understand the mechanism of floc formation and growth in electrocoagulation process, zeta potential and particle size measurements were done. The larger flocs and zeta potentials which closed to zero were observed at initial pH (pH(i)) 4 rather than pH(i) 5 and 6 for Al electrode. When zeta potential exhibited charge reversal, floc size reached to 5221 nm for pH; 4 at the current density of 1.2 mA/cm(2). The zeta potential remained negative over the whole pH range for Fe electrode. At pH(i) 4 and current density of 3 mA/cm(2), zeta potential value was -4.1 mV that indicate strong coagulation-flocculation. At these conditions, the maximum floc formation was 3042.3 nm. It can be concluded that, the removal of pollutant is due to charge neutralization and compression of double layer at lower initial pH value and sweeping and entrapment at higher pH. The removal efficiency of EC method was determined with respect to dissolved organic carbon (DOC) and UV/VIS absorbance at 254 and 436 nm reduction. Twenty-five minutes of process time with the aluminum electrode led to DOC removal of 87.5% with final DOC concentration of 2.01 mg/L and 91.1% UV-abs-254 removal was achieved after 2 min at pH(i) 4 and at current density of 1.2 mA/cm(2). The highest treatment efficiency for humic acid (HA) was 87% (DOCtreated 2.1 mg/L) at pH(i) 4 with iron electrodes. The short term best color removal (VIS absorbance at 436 nm) reduction performance was obtained with aluminum electrodes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Natural organic matter; Floc size; Humic acid; Electrocoagulation; Zeta potential